Internal migration trends in Malaysia / Saharani Abdul Rashid and Mazura Mokhtar - Abdul Rashid, Saharani; Mokhtar, Mazura (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
The rapid urbanisation experienced by many developing countries has resulted in higher demand for urban space and services. This study embarked into some empirical analysis to understand the dynamics of population movements in Malaysia and how this has shaped the population structure in this country. The urban and rural areas in Malaysia are shaped through time and by population shifts within and between its settlements. This study found that short distance migration is prominent in Malaysia, although the number of population migrated from one area to the other have decreased in recent years. In general, most of the more developed states have higher immigrants and all the less developed states have higher out-migrants during the more recent period. It can be concluded that development status of the state has attracted migrants from other states, probably in search of employment or other economic opportunities.